Journal of a slave dealer a view of some remarkable axcedents in the life of Nics. Owen on the coast of Africa and America from the year 1746 to the year 1757 /: a view of some remarkable axcedents in the life of Nics. Owen on the coast of Africa and America from the year 1746 to the year 1757. (2008) - Unknown
No abstract available